UPAYA PENINGKATAN MUTU PENDIDIKAN TINGGI SERTA IMPLIKASINYA TERHADAP TUGAS DAN PERAN DOSEN - Rizkan Syahbuddin (Universitas Islam Negeri Fatmawati Sukarno, 2018)
National development that lasts all the time, then the development of higher education is still prioritized by the government to continue to grow, including the role and duties of lecturers. Strategy setting is part of long-term development. The goal is in the most appropriate way in the future to be able. Improving the quality of higher education can not be separated from the quality of human resources owned. Therefore, improving the quality of the behavior and behavior of lecturers as teachers through education channels and effective training programs in their work is needed. With qualified human resources, it is expected that higher education will become an institution capable of effectively facing the challenges of the future.